A Post-Docking Role of Synaptotagmin 1-C2B Domain Bottom Residues R398/399 in Mouse Chromaffin Cells - Kedar, Girish H. (J Neurosci, 2015)
Synaptotagmin-1 (Syt1) is the principal Ca(2+) sensor for vesicle fusion and is also essential for vesicle docking in chromaffin cells. Docking depends on interactions of the Syt1-C2B domain with the t-SNARE SNAP25/Syntaxin1 complex and/or plasma membrane phospholipids. Here, we investigated the role of the positively charged “bottom” region of the C2B domain, proposed to help crosslink membranes, in vesicle docking and secretion in mouse chromaffin cells and in cell-free assays. We expressed a double mutation shown previously to interfere with lipid mixing between proteoliposomes and with synaptic transmission, Syt1-R398/399Q (RQ), in syt1 null mutant cells. Ultrastructural morphometry revealed that Syt1-RQ fully restored the docking defect observed previously in syt1 null mutant cells, similar to wild type Syt1 (Syt1-wt). Small unilamellar lipid vesicles (SUVs) that contained the v-SNARE Synaptobrevin2 and Syt1-R398/399Q also docked to t-SNARE-containing giant vesicles (GUVs), similar to Syt1-wt. However, unlike Syt1-wt, Syt1-RQ-induced docking was strictly PI(4,5)P(2)-dependent. Unlike docking, neither synchronized secretion in chromaffin cells nor Ca(2+)-triggered SUV–GUV fusion was restored by the Syt1 mutants. Finally, overexpressing the RQ-mutant in wild type cells produced no effect on either docking or secretion. We conclude that the positively charged bottom region in the C2B domain—and, by inference, Syt1-mediated membrane crosslinking—is required for triggering fusion, but not for docking. Secretory vesicles dock by multiple, PI(4,5)P(2)-dependent and PI(4,5)P(2)-independent mechanisms. The R398/399 mutations selectively disrupt the latter and hereby help to discriminate protein regions involved in different aspects of Syt1 function in docking and fusion. SIGNIFICANCE STATEMENT This study provides new insights in how the two opposite sides of the C2B domain of Synaptotagmin-1 participate in secretory vesicle fusion, and in more upstream steps, especially vesicle docking. We show that the “bottom” surface of the C2B domain is required for triggering fusion, but not for docking. Synaptotagmin-1 promotes docking by multiple, PI(4,5)P(2)-dependent and PI(4,5)P(2)-independent mechanisms. Mutations in the C2B bottom surface (R398/399) selectively disrupt the latter. These mutations help to discriminate protein regions involved in different aspects of Synaptotagmin-1 function in docking and fusion.